Issues and perspectives in global customer relationship management - Ramaseshan, Balasubramanian; Bejou, D.; Jain, S.; Mason, C.; Pancras, J. (Sage Publications, 2006)
Over the past few decades, cross-border business has experienced unparalleled growth. This growth is due to advances in communication and information technologies, privatization and deregulation in emerging economies, and emergence of the global consumer. As the era of globalization continues to manifest through the emergence of global companies, the importance of customer relationship management (CRM) in these companies has become increasingly significant. Global CRM (GCRM) is the strategic application of the processes and practices of CRM by firms operating in multiple countries or by firms serving customers who span multiple countries, which incorporates relevant differences in business practices, competition, regulatory characteristics, country characteristics, and consumer characteristics to CRM strategies to maximize customer value across the global customer portfolio of the firm. In this article, the authors present an overview of the GCRM environment and the challenges in formulation and implementation of CRM across national boundaries as a source of sustained advantage. The authors also provide a conceptual framework for GCRM and recommendations for future research in Global CRM.